Long‐term results for traumatic sternoclavicular joint dislocation treated with a sternoclavicular joint‐specific plate. Issue 4 (1st February 2021) - Wang, Shouli; Chen, Zhongyi; Lin, Lie; Pan, Qiaohong; Wang, Bin; Liu, Fucun; Zhang, Chuanyi
Abstract : This sternoclavicular joint (SCJ)‐specific plate is suitable for both anterior and posterior SCJ dislocations. Traumatic SCJ dislocation treated with an SCJ‐specific plate appeared to be efficient with satisfactory clinical and radiological results at long‐term follow‐up. Abstract: Background: The treatment of traumatic sternoclavicular joint (SCJ) dislocation (SCJD) with internal fixation has been reported with good short‐term results, but data on its long‐term results are scarce. Methods: Patients with traumatic SCJD treated with an SCJ‐specific plate between January 2003 and January 2018 were evaluated retrospectively. All implants were routinely removed. Data from radiography, the American Shoulder and Elbow Surgeons score, the visual analogue scale and abduction and forward elevation of the shoulder were collected and evaluated before the index surgery, at implant removal and at the latest follow‐up. Results: A total of 22 patients were included in this study with a mean follow‐up period of 94.8 months. All patients maintained good reduction after the index surgery and implant removal. The visual analogue scale significantly improved from 7.1 ± 1.3 before the index surgery to 0.9 ± 1.0 at implant removal ( P  < 0.001) and to 1.0 ± 1.1 at the latest follow‐up ( P  < 0.001); the American Shoulder and Elbow Surgeons score significantly improved from 37.9 ± 10.1 to 90.8 ± 7.8 ( P  < 0.001) and to 86.7 ± 8.6; and both abduction and forward elevation of the shoulder significantly improved at the latest follow‐up ( P  < 0.001). There was no significant difference in the clinical results after implant removal. Conclusion: Traumatic SCJD treated with an SCJ‐specific plate appeared to be efficient, with satisfactory clinical and radiological results at long‐term follow‐up.